2021
DOI: 10.5867/medwave.2021.06.8315
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to network meta-analysis for evidence synthesis

Abstract: This article belongs to a collaborative methodological series of narrative reviews about biostatistics and clinical epidemiology. The goal is to present basics concepts concerning the systematics reviews of multiple treatments comparisons with network meta-analysis. For clinical ques-tions with several therapeutic alternatives to be compared, the central question is how to classify or rank their effectiveness (benefit and harm) to choose the best option. The network meta-analysis aims to answer questions relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
1
7
0
3
Order By: Relevance
“…19 Other reviews have also noted that, when using the TIDieR checklist, reporting of conservative interventions is at best moderate and did not improve over time. 24,27,36,[72][73][74] Our scores were comparable to other recent reviews regarding most checklist items. [23][24][25]72 One review reported a low score (55% of studies) on the description of the rationale, theory, or goal of manipulations and mobilisations, 23 while we found that 86% of the studies described a clear rationale for using massage (often relaxation purposes).…”
Section: Discussionsupporting
confidence: 85%
“…19 Other reviews have also noted that, when using the TIDieR checklist, reporting of conservative interventions is at best moderate and did not improve over time. 24,27,36,[72][73][74] Our scores were comparable to other recent reviews regarding most checklist items. [23][24][25]72 One review reported a low score (55% of studies) on the description of the rationale, theory, or goal of manipulations and mobilisations, 23 while we found that 86% of the studies described a clear rationale for using massage (often relaxation purposes).…”
Section: Discussionsupporting
confidence: 85%
“…Es importante señalar que existen otras formas de síntesis sistemática de evidencia, que se abordan con más detalle en otras notas metodológicas de Medwave [6]. Entre ellas se encuentran las revisiones panorámicas y mapeos de evidencia [15], las revisiones rápidas [16], las revisiones vivas (de actualización continua) [17], los metanálisis en red [18] y las revisiones de revisiones sistemáticas (u overviews).…”
Section: Permite Considerar La Certeza De Los Resultadosunclassified
“…Existe un abordaje adicional llamado metanálisis en red (network meta-analysis), cuya metodología permite el uso de evidencia de comparaciones directas e indirectas. El detalle de este tipo de estudio está descrito en detalle en otro artículo de esta serie metodológica [18].…”
Section: Author Proofunclassified
“…Underlying the foundation of all network meta‐analyses is the assumption that transitivity is held true for every included indirect comparison [14]. Moreover, coherence must be maintained within all comparisons in the network [4]. Finally, heterogeneity among the direct comparisons should also be minimal in accordance with prior recommendations for traditional meta‐analyses as outlined in part 2 of this series.…”
Section: Conditions and Assumptionsmentioning
confidence: 99%